Superelastic cellular NiTi tube-based materials: Fabrication, experiments and modeling. (January 2015) - Machado, G.; Louche, H.; Alonso, T.; Favier, D.
Highlights: A study as a first step toward designing architectured NiTi materials. Cellular demonstrators were created joining tubes by electrical resistance welding. Modeling results were compared with compression tests performed on demonstrators. Contributions of the constitutive properties and architecture type were evaluated. Abstract: The aim of this paper is to present an experimental and modeling study as the first step towards designing and optimizing architectured materials constituted of NiTi tubes. The idea is to combine the intrinsic and novel properties of nickel–titanium shape memory alloys with purposely engineered topologies. By joining thin-wall superelastic tubes via electrical resistance welding, we create regular cellular material demonstrators. The superelastic behavior of two simple architectured materials based on identical tubes, but with two topologies, are experimentally characterized and modeled using finite element approaches. The predicted behaviors are compared by simulating complex loading, exploring the influence of the constitutive material behavior on the effective mechanical properties of cellular materials. The parameters of the constitutive equations are identified on tensile tests performed on small dog-bone shaped specimens, machined from the tubes by spark cutting. The modeling results are finally compared with compression tests performed on these simple architectured NiTi materials. As a further validation of the proposed study, two large cell structures (square and hexagonal stacking) were modeled to gain greater insight into the role of different architectures.